1995
DOI: 10.1063/1.113740
|View full text |Cite
|
Sign up to set email alerts
|

Ge/Pd (Zn) Ohmic contact scheme on p-InP based on the solid phase regrowth principle

Abstract: A contact metallization scheme of Ge/Pd(Zn), based on the solid-phase regrowth principle, has been developed for the formation of Ohmic contact on p-InP. Typical contact resistivities of low 10−4 to low 10−5 Ω cm2 can be obtained after annealing at temperatures higher than 400 °C. Cross-sectional transmission electron microscopy study confirmed the solid-phase regrowth process in the InP substrate. Precipitates of trapped materials during solid phase regrowth have also been observed. A solid phase regrowth mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The obtained minimum resistivity values conform to the moderate doping level of the InGaP epitaxial layers ( p % 2 Â 10 18 cm --3 ) and in spite of the larger bandgap ($1.9 eV) of InGaP, they are fully comparable to those for alloyed Au(Be, Zn) [5,18] and non-alloyed Ge/Pd(Zn) [14,15] Ohmic contacts to p-type InP with similar doping concentration.…”
Section: Electrical Propertiesmentioning
confidence: 55%
See 1 more Smart Citation
“…The obtained minimum resistivity values conform to the moderate doping level of the InGaP epitaxial layers ( p % 2 Â 10 18 cm --3 ) and in spite of the larger bandgap ($1.9 eV) of InGaP, they are fully comparable to those for alloyed Au(Be, Zn) [5,18] and non-alloyed Ge/Pd(Zn) [14,15] Ohmic contacts to p-type InP with similar doping concentration.…”
Section: Electrical Propertiesmentioning
confidence: 55%
“…Most of the effort, however, has been devoted to the development of low-resistance, shallow, non-Au-based Ohmic contacts, particularly those where the Au contact layer is replaced by Pd. As far as we know, a comprehensive study of the solid-phase regrowth process [7] to form low-resistance non-spiking Pd-based contacts has been reported for GaAs and GaAlAs [8][9][10], InGaAs [11,12], InP and InGaAsP [13][14][15][16], but not for p-type InGaP.…”
Section: Introductionmentioning
confidence: 99%
“…12 Later, Pd/ Ge(Zn) contacts on p-InP with Zn evaporated were shown to exhibit resistivities comparable to the lowest values for Au-based metallizations on this material (ρ c ≥ 1 × 10 -5 Ωcm 2 ). 13 Record low resistivities (≈ 5 × 10 -6 Ωcm 2 ) were achieved on p-InP with Pd/Sb(Zn) contacts, which were shown to conform to the SPR principle. 14 In a preliminary paper, the authors reported both low contact resistivity (ρ c = 3-8 × 10 -7 Ωcm 2 ) and penetration depth (<50 nm) for Pd/Sb(Zn) and Pd/Ge(Zn) contacts with Zn evaporated on moderately doped In 0.53 Ga 0.47 As (p = 4 × 10 18 cm -3 ).…”
Section: Introductionmentioning
confidence: 79%
“…23,24) For the p-InP ohmic contacts, Wang et al developed PdGe(Zn) contacts using SPR process. 4) From the XRD and XTEM study of Sb/Zn/Pd contacts, Pd in the contact materials was found to react with InP to produce ternary Pd 2 InP compounds at the contact metals/InP interface. This compound was kinematically stable at 400…”
Section: Role Of Pd Third Layermentioning
confidence: 99%
“…Wang et al 4) developed Pd/Zn/Pd/Ge ohmic contacts using the solid-phase regrowth technique and achieved the contact resistance as low as 4 × 10 −5 cm 2 by annealing at 500…”
Section: Introductionmentioning
confidence: 99%